2019
DOI: 10.1021/acschembio.9b00354
|View full text |Cite
|
Sign up to set email alerts
|

Fast Fluorescence Lifetime Imaging Reveals the Aggregation Processes of α-Synuclein and Polyglutamine in Aging Caenorhabditis elegans

Abstract: The nematode worm Caenorhabditis elegans has emerged as an important model organism to study the molecular mechanisms of protein misfolding diseases associated with amyloid formation because of its small size, ease of genetic manipulation and optical transparency. Obtaining a reliable and quantitative read-out of protein aggregation in this system, however, remains a challenge. To address this problem, we here present a fast time-gated fluorescence lifetime imaging (TG-FLIM) method and show that it provides fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…In line with previous reports [47], we observed age-dependent coalescence of a-synuclein-YFP into distinct cytoplasmic inclusions ( Figure 1A). Previous fluorescence recovery after photobleaching (FRAP) and FLIM studies have suggested that asynuclein in inclusions exists in a mobile, non-amyloid state [44][45][46][47]. Here, we performed high resolution FLIM to be able to differentiate the protein localised at inclusions from the diffuse (non-aggregated) pool (Figure 1A).…”
Section: A-synuclein Forms Non-amyloid Inclusions In C Elegansmentioning
confidence: 92%
See 1 more Smart Citation
“…In line with previous reports [47], we observed age-dependent coalescence of a-synuclein-YFP into distinct cytoplasmic inclusions ( Figure 1A). Previous fluorescence recovery after photobleaching (FRAP) and FLIM studies have suggested that asynuclein in inclusions exists in a mobile, non-amyloid state [44][45][46][47]. Here, we performed high resolution FLIM to be able to differentiate the protein localised at inclusions from the diffuse (non-aggregated) pool (Figure 1A).…”
Section: A-synuclein Forms Non-amyloid Inclusions In C Elegansmentioning
confidence: 92%
“…To understand the initial events in the a-synuclein aggregation process, we assessed its selfassociation using confocal fluorescence lifetime imaging (FLIM) in the nematode worm Caenorhabditis elegans. The fluorescence lifetime of a fluorophore has been previously shown to be an accurate measure of protein self-assembly and amyloid formation, independent of protein concentration or fluorescence intensity [44][45][46]. Given the optical transparency and well-established genetics of C. elegans, we sought to compare the fluorescence lifetime of a human a-synuclein-YFP fusion protein expressed in body wall muscle cells (OW40 worm model, see Methods).…”
Section: A-synuclein Forms Non-amyloid Inclusions In C Elegansmentioning
confidence: 99%
“…Furthermore, the use of biosensors in combination with fluorescence microscopy may shed more light on the conformational state of protein aggregates in vivo , as demonstrated e.g. by the changes in the fluorescence lifetime of protein tags upon amyloid formation (Kaminski Schierle et al ., 2011 a ; Laine et al ., 2019).…”
Section: Methodological Challengesmentioning
confidence: 99%
“…Whether phase separation drives tau aggregation in human disease remains to be determined, and it will be exciting to study this phenomenon in in vivo models, e.g. by using fluorescence lifetime imaging microscopy (FLIM, Table 1) in Caenorhabditis elegans (Laine et al ., 2019) (see Section ‘α-Synuclein models’).…”
Section: Determination Of Protein Aggregation Mechanisms Using In Vitmentioning
confidence: 99%
See 1 more Smart Citation